A single-chain variable region immunoglobulin library from the abomasal lymph node of sheep infected with the gastrointestinal nematode parasite Haemonchus contortus - White, Greg; Meeusen, E.; Newton, S. (ELSEVIER, 2001)
Sheep immunoglobulin (Ig) heavy-chain (VHDJH) and lambda light-chain variable region (VlJl) nucleotide coding sequence was isolated by reverse transcriptase-polymerase chain reaction (RTPCR) from abomasal lymph node (ALN) B cells of immune sheep challenged with the gastrointestinal nematode parasite Haemonchus contortus. Single-chain antibodies (scFv) were then constructed with the purified VHDJH and VlJl Ig gene region DNA using oligonucleotides to PCR and join the variable regions to a central [Gly4Ser]3-linker. In a similar fashion 5'-SfI and 3'-NotI restriction endonuclease sites were added for cloning into a phagemid expression vector. Expression of sheep scFv from pHFA phagemid in an amber-suppresser strain of Escherichia coli, after infection with filamentous phage, resulted in 109 sheep scFv antibodies displayed as a library on phagemid particles. Western blot analysis demonstrated sheep scFv gene expression in E. coli celllysate and on purified library phage. In addition, four rounds of scFv-library selection against H. contortus surface antigen resulted in a 300-fold increase in the elution titre of phage recovered from parasite surface antigen. Nearly 1000 of the selected and eluted scFvs were expressed in an attempt to identify monoclonal sheep scFv against parasite antigen. Only low affinity clones were isolated during screening of this sheep scFv-library, suggesting different strategies will be needed for isolation of specifc high affinity recombinant antibody in future studies.